Implementation and evaluation of the clinical pathway for the diagnosis and treatment of acute coronary syndrome - Dhital, Bishnu Mani; Mao, Ou Yang; Regmi, Shyam Raj; Regmi, Sudhir (Journal of Chitwan Medical College, 2018)
Background: The clinical pathways have been developed to guide and standardize diagnosis, treatment of certain diseases, optimize smooth patient care, and its application has been proven to regulate the medical practice and to improve the quality of medical care in developed countries. Objective: To analyze and evaluate the diagnosis and treatment of acute coronary syndrome (ACS) after the implementation of clinical pathways and to identify the areas need to be improved in clinical practice in Xiangya Third Hospital of Central South University. Methods: 250 ACS patients, divided into five groups 50 in each, were collected from December 2009 to December 2011, the first group was considered as baseline and compared with other four group. All these data were compared and analyzed with other tertiary hospitals of china. Results: STEMI patients arriving within 12 hours of onset of symptoms was increased (P<0.05), and final diagnosis consistent with cardiac markers was also increased (P<0.05).Use of aspirin, clopidogrel, β-Blocker, ACEI /ARB, and statin was higher (P>0.05), but the use of clopidogrel and statin was significantly higher (P<0.05) than other hospitals; no significant difference (P>0.05) in Door-to-needle time or Door-to-balloon time, though longer than standard guidelines, but the door-to-needle time was shorter when compared with other hospitals. TIMI risk score of UA/NSTEMI patients and invasive therapy (PCI) was negatively correlated (r = -0.312, P<0.05), and results were similar when compared with other hospitals; high-risk patients increased, but no significant difference in mortality (P>0.05). Conclusion: Implementation of Clinical pathway may help to improve patient outcome with early invasive and medical therapy.